Quality of Recovery Following Orthopedic Surgery in Patients at an Academic Hospital in South Africa. (26th May 2021) - Wessels, Erica; Perrie, Helen; Scribante, Juan; Jooma, Zainub
Abstract : BACKGROUND: Measurement of perioperative quality of recovery (QoR) is an important tool in improving the patient's perioperative experience. By making use of the Quality of Recovery-15 (QoR-15) questionnaire, this study aimed to measure the QoR on day 1 in patients following elective and semiurgent orthopedic surgery at an academic hospital. A secondary aim was to determine factors that may influence the QoR. METHODS: A cross-sectional research study was performed in 122 patients presenting for elective and semiurgent orthopedic surgery during core working hours between July and November 2019 at Helen Joseph Hospital, Johannesburg, South Africa. Patients completed a baseline QoR-15 assessment preoperatively and a day 1 QoR-15 assessment between 12 and 24 hours postoperatively. Additional information on various anesthetic, surgical, and patient factors was collected. RESULTS: Nineteen patients (15.6%) had a poor QoR on day 1 and were found to have started with a significantly worse baseline QoR-15 score than those with no poor QoR (98.5 vs 128.5; P < .001). A significant worsening from the overall mean baseline QoR-15 to the overall mean day 1 QoR-15 score was found (123.8 vs 113.1; P = .001). This worsening score was more pronounced in patients with a poor day 1 QoR-15 score than no poor day 1 score (25.3 vs 8; P = .002). Surgical site was found to have a significant effect on day 1 score ( P = .026). A significantly worse severe pain score was found in patients with foot/ankle and knee surgery compared to hand/arm surgery ( P = .012 and P = .032, respectively) and is thought to be due to the decreased use of peripheral nerve blocks in lower limb surgery. Sex, American Society of Anesthesiologists (ASA) physical status, type of anesthesia, postoperative analgesia, and antiemetic given (only applicable in general anesthetic cases) were not found to have a significant effect on the day 1 QoR-15 scores. CONCLUSIONS: Patients who had a poor QoR on day 1 started with a significantly worse baseline QoR-15 score and experienced a significantly greater negative change in the mean difference. Preoperative identification of patients who are at risk of a poor postoperative QoR may aid in preemptive targeting of limited resources to those who need them most. Postoperative pain, particularly in patients after foot/ankle and knee surgery, is a significant modifiable factor to improve postoperative QoR at our institution.